Job Satisfaction among Vocational High School Teachers by Demographics Factors In Educational Institutions - Umi Anugerah Izzati; Olievia Prabandini Mulyana; Meita Santi Budiani; Ni Wayan Sukmawati Puspitadewi; Mayang Salsabila; Christopher Robert Muljo (IJORER : International Journal of Recent Educational Research, 2023)
Objective: Job satisfaction is an essential factor that needs attention from leaders in educational institutions. If teachers in educational institutions have job satisfaction, this will impact their job performance. This study analyzes job satisfaction from demographic factors of age, gender, tenure, and marital status of vocational high school teachers in Surabaya. Method: This study used quantitative methods. This research was conducted in educational institutions, especially in vocational high schools. The subjects of this study used 160 vocational high school teachers in Surabaya. The sampling technique used convenience. The data analysis technique used an independent sample t-test. The results of this study indicate that there are differences in job satisfaction by demographic elements consisting of age, tenure, gender, and marital status. Results: The results of this study indicate that teachers who are more than 35 years of age have higher satisfaction, teachers who have more than five years of tenure have higher job satisfaction, female teachers have higher job satisfaction than male teachers, and married teachers have higher job satisfaction than unmarried teachers. Novelty: Previous research has studied the impact of job satisfaction, but to researchers' knowledge, more research is needed to study job satisfaction from demographic factors in vocational high school teachers. Therefore, this topic is interesting to study, considering that demographic factors are a point of view that is rarely used to study individual variables.